Determination of riboflavin in dragee “Revit” by HPLC - B. О. Varynskyi; M. Yu. Zeleniuk; A. H. Kaplaushenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of the work is development of express, selective, reproducible methods for the determination of riboflavin by HPLC in a multivitamin preparation, dragee “Revit”.